Pengaruh Komposisi Media Tanam terhadap Pertumbuhan Bawang Prei (Allium porrum L.) - Zhalwa Faradiyah; Titi Laily Hajiriah; Sucika Armiani (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This research was conducted at the Experimental Park which is located at Jalan Segaranak Number 08 Ampenan, Mataram City, West Nusa Tenggara Province, from May 2022 to August 2022. This research has objectives, namely: 1) to determine the influence of the media planting on the growth and yield of leek (Allium porrum L.) when placed on growing media with different compositions; and 2) to evaluate the composition of the best planting medium used for leek (Allium porrum L.) growth. The method used was a completely randomized design (CRD) with 5 treatments, namely P0 = 100% soil, P1 = 50% soil: 50% organic fertilizer, P2 = 50% soil: 25% organic fertilizer: 25% charcoal husk, P3 = 50% soil: 25% organic fertilizer: 25% sawdust, P4 = 50% soil: 25% organic fertilizer: 25% coconut fiber, with 4 replications to obtain 20 experimental units. The results of this study were analyzed by one-way ANOVA test with a significance level of 0.05 for 4 parameters, namely: plant height, root length, number of leaves, and plant fresh weight. Data were analyzed using the one-way ANOVA test and then followed by using the BNT 0.05 test. Based on the results of the research conducted, it can be seen that the planting media has a significantly different effect on Sig. <0.05 on plant height, plant root length, and fresh weight of leek (Allium poruum L.) plants. Meanwhile, on the parameter of many leaves, the planting medium did not have a significantly different effect on Sig. >0.05.